The Impact of Relative Contribution of Psychological Capital and Academic Inclusion in Predicting the Quality of Life among Female University Students in Saudi Arabia - Almotrefi, Norah Abdulrahman (Journal of Educational and Psychological Sciences, 2025)
The current research aims to examine the interrelations of academic inclusion, psychological capital, and the quality of life of students among university students, and to determine the significance of the regression coefficient to predict the quality of life of students through psychological capital and academic inclusion. The correlational descriptive approach was employed in the research, due to its suitability to the nature and objectives of the current research. The sample comprised 360 female students randomly selected from the students of the academic years (second, third, and fourth) at an academic institution in Saudi Arabia, distributed over different divisions, with an average age of (19.80) years, and a standard deviation of (0.90) years. It is noted that the basic study sample did not include any of the members of the survey sample. The researcher prepared the tools of the study including Psychological Capital Scale, Academic inclusion, and Quality of students' life scale. After statistical processing of the data, the study found a positive and significant relationship at (0.01) between academic inclusion and psychological capital ranging from (0.536) to (0.862). In addition, findings showed a significant relationship at (0.01) between psychological capital and the quality of life of students, and a significant relationship at (0.01) between the quality of life of students and academic inclusion in the research sample, which ranged from (0.523) to (0.853) at the level of 0.01. The results of the multiple linear regression model showed that the regression model is significant through the (F) value of (2891.23) which confirms that psychological capital contributes to predicting the quality of university life, and it is significant through the (F) value of (7661.022) with a significance of (0.00) which confirms that academic inclusion also contributes to predicting the quality of students' life. However, the results concluded that academic inclusion`s effect is greater than psychological capital concerning the quality of student life. These findings underline the need to prioritize positive psychology fields and academic inclusion programs to enhance students' well-being and equip them with the skills necessary for personal and academic success. It also highlights the necessity of integrating awareness programs and guidance programs within university courses that help students develop cognitive, psychological, social, and academic skills to perform in both academic and professional life.
Keywords: academic inclusion; psychological capital; quality of students` life